Health Screenings and Education on Healthy Lifestyles as a Strategy for the Early Detection of Noncommunicable Diseases Among the Community in Cibodas Village - Priantono, Ferry; Fadilla, Alya Syifa; Nafisah, Nani; Selviyani, Selviyani; Palah, Muhamad Pajrul; Machfud, Muhammad Salim; Apriansyah, Irvan Agung; Kurniawan, Kurniawan; Koesmawan, Koesmawan; Priyana, Yana (Jurnal Pengabdian West Science, 2026)
The prevalence of noncommunicable diseases (NCDs) such as hypertension and diabetes mellitus continues to rise, including in rural areas. Low public awareness of the importance of regular health checkups exacerbates this situation. This community service activity aims to improve residents’ knowledge through free health screenings (blood pressure, random blood glucose) and education on healthy lifestyles in Cibodas Village, Parung Kuda Subdistrict, Sukabumi Regency. The method used was a participatory approach involving health screenings, individual consultations, and interactive health education sessions for 25 residents. Blood pressure test results for the 25 participants showed that 31.8% had hypertension (stages 1 and 2) and 59.1% were in a prehypertensive state. Random blood glucose testing of 15 participants found that 13.3% had diabetes (≥200 mg/dL) and 40% had prediabetes (140–199 mg/dL); most were unaware of their condition. Following the education session, there was an increase in understanding regarding the importance of early detection and a commitment to undergoing regular check-ups. In conclusion, health screening integrated with education proved effective in revealing the hidden burden of NCDs and improving health literacy among the rural community.
Keywords: health checkups; early detection; noncommunicable diseases; health education